2018
DOI: 10.3892/mmr.2018.8969
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatics analysis of key differentially expressed genes in well and poorly differentiated endometrial carcinoma

Abstract: Endometrial carcinoma (EC) is one of the most common gynecological malignancies. The malignant degree increases between grade (G)1 and G3, and EC of G3 usually presents a high recurrence rate and poor prognosis. Therefore, the present study aimed to examine the principal genes associated with the degree of differentiation in EC. The microarrays GSE17025, GSE24537 and GSE35784, representing data of Type I EC samples of G1 and G3, were downloaded from the Gene Expression Omnibus. The differentially expressed gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 44 publications
1
4
0
Order By: Relevance
“…Gene expression profiles revealed three distinctive gene clusters, with genes upregulated (clusters I and II) or downregulated (cluster III) in grade 3 tumors in comparison to grade 1 tumors. These results are in line with a recent study reporting the identification of genes and microRNAs (miRs) differentially expressed in grade 3 EC and functionally associated with cell cycle regulation ( 43 ).…”
Section: Discussionsupporting
confidence: 91%
“…Gene expression profiles revealed three distinctive gene clusters, with genes upregulated (clusters I and II) or downregulated (cluster III) in grade 3 tumors in comparison to grade 1 tumors. These results are in line with a recent study reporting the identification of genes and microRNAs (miRs) differentially expressed in grade 3 EC and functionally associated with cell cycle regulation ( 43 ).…”
Section: Discussionsupporting
confidence: 91%
“…We also discovered miRNA changes that target genes controlling the transformation of normal endometrial tissue to aggressive malignant ones. High estrogen level, overweight, diabetes mellitus and other human disorders that are known to raise the risk of endometrial cancer can be better understood by finding hub genes, with the highest degree of centrality in the key module ( Zang et al, 2018 ). Therefore, when generating miRNA-mRNA functional network that are composed of 66 miRNA target genes and 26 miRNAs, we identified 18 hub target genes and 5 miRNAs with a high degree of centrality parameter (>50).…”
Section: Discussionmentioning
confidence: 99%
“…The CCNB1 gene encodes an important regulator of the cell cycle and is associated with cyclin-dependent kinase 1, and it is also known to regulate the G 2 /M transition during mitosis (62). It has been previously reported that CCNB1 expression is associated with poorly differentiated EC (7). Integrated bioinformatics analysis methods were used to examine TCGA and GEO datasets (26).…”
Section: Discussionmentioning
confidence: 99%
“…High-grade stage I UCEC progresses rapidly and presents with a high metastatic rate within a short time (6). Higher-grade classification takes into account the number of tumor cells undergoing differentiation, which allows the more malignant biological behavior to be observed (7). High-grade UCEC frequently presents with lymph-vascular space invasion and deep myometrial infiltration (8).…”
Section: Introductionmentioning
confidence: 99%